Evolution of the Fermi surface of BaFe2(As1-xPx){2} on entering the superconducting dome. - Shishido, H; Bangura, A; Coldea, A; Tonegawa, S; Hashimoto, K; Kasahara, S; Rourke, P; Ikeda, H; Terashima, T; Settai, R; Onuki, Y; Vignolles, D; et al. (2010)
Using the de Haas-van Alphen effect we have measured the evolution of the Fermi surface of BaFe2(As1-xPx){2} as a function of isoelectric substitution (As/P) for 0.41